Biology and immature stages of a lonchaeid fly, Earomyia crystallophila (Becker, 1895) (Diptera, Lochaeidae), developing in stems of Veratrum album L. - Ozerov, A.l.; Krivosheina, M.g. (Zootaxa, 2017)
The development of lonchaeid flies of the genus Earomyia Zetterstedt, 1842 (Diptera: Lochaeidae) in Veratrum album L. stems is reported for the first time. Larvae were collected in July 2015 in Serbia (Crni Vrh) in mountains at 988 m a.s.l. from inside a blackened decaying part of the stem at a point 1/3 from the apex. No other insects were discovered in the same part of stem. Emergence of adult E. crystallophila (Becker, 1895) occurred under laboratory conditions in January 2016. The larva and puparia are described for the first time.